Quality of life after percutaneous vertebroplasty in patients after traumatic vertebral compression fractures - Voloshchuk, Оleksandr S.; Krasylenko, Olena P. (Ukrainian Neurosurgical Journal, 2019)
Objective. To analyze the effectiveness of percutaneous vertebroplasty (PV) based on the quality of life (QOL) evaluation in the short-term and long-term postoperative periods in patients with traumatic vertebral compression fractures (VCF). Materials and methods. The quality of life was analyzed in 160 patients after PV in the Department of Miniinvasive and Laser Spinal Neurosurgery in Romodanov Neurosurgery Institute of NAMS of Ukraine in 2002–2016. Results. Before the operation, the Oswestry Disability Index (ODI) was 57.7±1.6 % that corresponded to severe disability; in the early post-operative period, in 3 days after intervention, it significantly (p <0.001) decreased to 31.2±1.3 %, that corresponded to moderate disability. After 3 months, the ODI decreased to 18.8±1.4 % (p <0.05), demonstrating minimal disability. After 6 months, there was a tendency to further decreasing of ODI (18.5±1.4 %). In the long-term postoperative period, there were no significant changes in QOL and, consequently, the disability grade: after 1 year, ODI was 18.4±1.3; in 3 years — 18.2±1.3; in the period over 3 years — 18.3±1.3, that corresponded to the minimum disability. There was no significant difference in the short-term and long-term PV outcomes in patients from different age groups. Conclusions. This analysis showed that PV allows significantly reduce the disability grate in patients of any age with isolated traumatic VCF and significantly improve their QOL as soon as possible. The functional results of this pathology treatment with PV technique remain positive for a long (up to 12.5 years) observation period.